Chalandise ou expertise(s) : le développement économique des clubs professionnels de sport indoor. Étude de cas de trois clubs du Nord - Terrien, M.; Valin, G.; Jugé, R. (Movement & Sport Sciences - Science & Motricité, 2021)
This paper deals with the economic development of the clubs in the male first division of basketball, handball and volleyball. Several exogenous factors could coerce those professional clubs such as local potential of the city or a lack of attractiveness for major media. Therefore, those organizations have a small margin to develop themselves. Nevertheless, a documentary analysis allows light to be shed on the transformation of the economic model of the handball clubs. The results suggest the importance of the endogenous factors, especially the commercial expertise, in this shift. The arrival of a magnate in this league indeed implied the other clubs to improve their functioning to remain competitive. Multiple case studies (one club per league) confirm those results. When the clubs give themselves the means, they are able to attract new sources of income and then to reduce the weight of subsidy in their budget.